Eliciting Plant Defenses Through Herbivore-Induced Plant Volatiles’ Exposure in Sweet Peppers - Riahi, Chaymaa; González-Rodríguez, Jhonn; Alonso-Valiente, Miquel; Urbaneja, Alberto; Pérez-Hedo, Meritxell (Frontiers in Ecology and Evolution, 2022)
Insect herbivory activates plant defence mechanisms and releases a blend of herbivore-induced plant volatiles (HIPVs). These volatile compounds may be involved in plant-plant communication and induce defence response in undamaged plants. In this work, we investigated whether the exposure of sweet pepper plants to HIPVs [(Z)-3-hexenol, (Z)-3-hexenyl acetate, (Z)-3-hexenyl propanoate, (Z)-3-hexenyl butanoate, hexyl butanoate, methyl salicylate and methyl jasmonate] activates the sweet pepper immune defence system. For this, healthy sweet pepper plants were individually exposed to the each of the above mentioned HIPVs over 48h. The expression of jasmonic acid and salicylic acid related genes was quantified. Here, we show that all the tested volatiles induced plant defences by upregulating the jasmonic acid and salicylic acid signalling pathway. Additionally, the response of Frankliniella occidentalis, a key sweet pepper pest, and Orius laevigatus, the main natural enemy of F. occidentalis, to HIPV-exposed sweet pepper plants were studied in a Y-tube olfactometer. Only plants exposed to (Z)-3-hexenyl propanoate and methyl salicylate repelled F. occidentalis whereas O. laevigatus showed a strong preference to plants exposed to (Z)-3-hexenol, (Z)-3-hexenyl propanoate, (Z)-3-hexenyl butanoate, methyl salicylate and methyl jasmonate. Our results show that HIPVs act as elicitors to sweet pepper plant defences by enhancing defensive signalling pathways. We anticipate our results to be a starting point for integrating HIPVs-based approaches in sweet pepper pest management systems which may provide a sustainable strategy to manage insect pests in horticultural plants.